Characteristics of metadynamic recrystallization of Nimonic 80A superalloy. Issue 4 (6th February 2015) - Gu, Sendong; Zhang, Chi; Zhang, Liwen; Shen, Wenfei
Abstract: Abstract : The metadynamic recrystallization (MDRX) behaviors in deformed Nimonic 80A superalloy were investigated by isothermal interrupted hot compression tests on a Gleeble-1500 thermo-mechanical simulator. Compression tests were performed using double hit schedules in the deformation temperature range of 1050–1150 °C, the interpass time range of 0.5–10 s, the strain rate range of 0.01–4 s −1, and the prestrain range of 0.30–0.50. To characterize the MDRX behaviors of the alloy, the effects of deformation temperature, strain rate, and prestrain on the metadynamic softening and recrystallized grain size were analyzed. The results reveal that the effects of deformation temperature and strain rate on the metadynamic softening fraction and recrystallized grain size are significant. However, the effects of prestrain on the metadynamic softening fraction and recrystallized grain size are not very marked and can be neglected. Then, by regression analysis of the experimental data, the MDRX kinetic model and recrystallized grain size model were proposed. The predicted results show good agreement with the experimental ones, which indicates that the proposed models can give an accurate prediction of the softening behaviors and microstructural evolution for Nimonic 80A.